Development of a comprehensive bilateral trade-flow dataset of the environmental pressures of global food production - Joseph M. DeCesaro; Edward H. Allison; Gage Clawson; Haley K. Epperly; Melanie Frazier; Halley E. Froelich; Jessica A. Gephart; Kirsty L. Nash; David R. Williams; Benjamin S. Halpern (Environmental Data Science)
The global food system puts enormous pressure on the environment. Managing these pressures requires understanding not only where they occur (i.e., where food is produced), but also who drives them (i.e., where food is consumed). However, the size and complexity of global supply chains make it difficult to trace food production to consumption. Here, we provide the most comprehensive dataset of bilateral trade flows of environmental pressures stemming from food production from producing to consuming nations. The dataset provides environmental pressures for greenhouse gas emissions, water use, nitrogen and phosphorus pollution, and the area of land/water occupancy of food production for crops and animals from land, freshwater, and ocean systems. To produce these data, we improved upon reported food trade and production data to identify producing and consuming nations for each food item, allowing us to match food flows with appropriate environmental pressure data. These data provide a resource for research on sustainable global food consumption and the drivers of environmental impact.